Analisis Perubahan Bentuk Ruang pada Rumah Adat Karo di Desa Lingga - Dasrizal Dasrizal; Asri Afriliany Surbakti; Sandros Timoti Tambun; Aroli Harefa (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
Traditional houses are authentic historical-cultural heritage architecture and full of philosophy. One of them is the Karo Traditional House which is commonly called Siwaluh Jabu because it is inhabited by eight heads of families. Changes in human behavior due to the growing modernization process caused significant changes in the shape of the space in the Karo Traditional HouseThe change in the shape of the space in the karo traditional house occurs because there is no longer a desire to inhabit and build a traditional house due to friction of theft problems, social relations between families that are not in harmony, children cannot studied because of the noisy and crowded house conditions, and the interior completeness that is not possible. Some of these factors have resulted in a decrease in the concern of the Karo people for their traditional houses, which in the end there have been several changes in the spatial patterns of Karo traditional houses.The purpose of this study was to determine the shape of the space in the Karo traditional house in Lingga Village and the changed  in the shape and function of the space that occur in the Karo traditional house today. To achieve this goal, this research was carried out using a qualitative description method, where researchers made direct observations and conduct interviews with the local community. As a mandatory output of research, scientific articles will be published in nationally accredited journals.